2019
DOI: 10.3389/fpsyg.2019.01232
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Predict an Athlete’s Behavior? The Use of Polar Coordinates to Identify Key Patterns in Taekwondo

Abstract: Match analysts and sport psychologists can help elite athletes develop planned competition strategies from a technical-tactical perspective by analyzing of previous performances. The aim of this study was to analyze the behavioral patterns used to score points in the 2012 London Olympic Games by a mixed observational methodology and polar coordinate analysis. This analysis is a representation of four quadrants of the relationships between focal behavior [i.e., scoring, (SC)] and conditioned behaviors as key fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 41 publications
2
20
0
6
Order By: Relevance
“…As such, it is difficult to compare our results with those of previous studies. The main findings of the present study are that there are specific behaviors used by taekwondo elite athletes to achieve different scores, in accordance with previous studies that consider tactics, techniques, and the kicking zone to be related to score (Matsushigue et al, 2009;Falcó et al, 2012;Falco et al, 2014;Sledweski et al, 2015;Menescardi et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As such, it is difficult to compare our results with those of previous studies. The main findings of the present study are that there are specific behaviors used by taekwondo elite athletes to achieve different scores, in accordance with previous studies that consider tactics, techniques, and the kicking zone to be related to score (Matsushigue et al, 2009;Falcó et al, 2012;Falco et al, 2014;Sledweski et al, 2015;Menescardi et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, anticipatory counterattacks and spinning kicks were related to effective two-point actions, while threepoint actions were related to circular techniques, the most frequently performed in competitions (Matsushigue et al, 2009). Finally, Menescardi et al (2019) found different patterns between male and females in one-point actions: female scored one point after cut, direct attacks with circular techniques to the chest, while males scored after spinning anticipate counterattack and dodges. Females scored two points after direct attacks while males used simultaneous counterattacks to the head.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Taekwondo researchers and trainers have already started working on modeling to "provide objective data on competitive behavior" (Menescardi et al, 2019). Their study focuses on technical and tactical behaviors and the regulations that need to be made concerning their inclusion in trainings, and of course, in bouts.…”
Section: Points Scored Simultaneously Flags and Senshumentioning
confidence: 99%
“…According to Menescardi et al (2019), "objective data regarding successful behavioral patterns, (. .…”
Section: Current Situation Penalties Possible Strategic Actionsmentioning
confidence: 99%